El cambio de jurisprudencia del Consejo de Estado, respecto de la caducidad para casos de delitos de lesa humanidad, análisis de la incidencia económica en el departamento de Casanare. - Coronado, Iván Darío Vega; Ayala, Corina Duque (Revista Pensamiento Americano)
Objective: This academic article originated from the need to make a deep analysis and a subsequent criticism of the jurisprudential change, the one that is effectuated by the Honorable Council of State (Expiration for public damages derived from crimes against humanity - Petition Control for Direct Reparation, 2020). Conclusions: In whose unification judgment changed the governmental regulations, and determined that victims from the so-called False Positives have a precise term of two years to sue the National Government in Integral Reparation Searching. That is why it takes an initial reference by mere suspicion in what facts were immersed in national government forces.